SMART Monitoring computer program for oral and skin lesions measurements: analysis through clinical photography - Witt, Pedro Senna; Zimmer, Vithória Rabelo; Smiderle, Fabiane; Grando, Liliane Janete; Girondi, Juliana Balbinot Reis; Caldas, Ricardo Armini; Rabelo, Gustavo Davi (Journal of Oral Diagnosis, 2024)
Lesion evaluation through photographs is a common clinical practice and its performance using computational tools is encouraged. Objective: To assess the reliability of the computer program SMART Monitoring (SM) in giving adequate lesion measurements through clinical photography. Materials and methods: A cross-sectional study was conducted with 28 patients diagnosed with oral or skin flat lesions. Each lesion was measured twice: clinically and by photographic image. Photographs were taken using a 3D-printed scale as a reference for SM measurements of the total lesional area (mm²) and the two longest axes (length and width) by two different operators. The agreement was evaluated between the axis’s measurements of the two operators with the clinic measurements by the Bland-Altman plot. Results: Both operators revealed excellent agreement (ICC=0.98) regarding measurements of the lesion’s axes and the total lesional area with no difference between operators. Comparison of the axes’ values from SM to clinical measurements were also not different (p=0.82 and p=0.43). The Bland-Altman plot revealed that most mean differences were within the 95% confidence interval. Conclusion: SMART Monitoring proved to be a reliable tool for measuring oral or skin flat lesions on clinical photographs, regarding length, width, and total area measurements. The values obtained using SMART Monitoring presented an excellent agreement with the clinical measurements.